Influence of flange dimensions and geometrical imperfections on stress concentrations at welded flange necks. Issue 11 (31st July 2020) - Seidel, Marc; Wegener, Filip; van Dijk, Ingmar
Abstract: Ring flange connections for tubular towers, like those for wind turbines or chimneys, are subjected to significant fatigue loading. Next to the bolts, the weld connecting the flange to the tower shell also needs to be checked against fatigue failure. The flange causes local bending moments in the shell, which increase the meridional stress, i. e. stress concentrations occur. In this paper, the influence of geometrical imperfections on such stress concentrations is quantified and the influence of flange geometry on resulting stress is investigated. Recommendations are given for flange dimensions and the design procedure. Abstract: Einfluss von Flanschabmessungen und geometrischen Imperfektionen auf Spannungskonzentrationen an Schweißnähten von Ringflanschverbindungen Ringflanschverbindungen für Rohrtürme, wie solche für Windenergieanlagen oder Schornsteine, sind einer erheblichen Ermüdungsbelastung ausgesetzt. Neben den Schrauben muss auch die Schweißnaht, die den Flansch mit der Turmschale verbindet, gegen Ermüdungsversagen abgesichert werden. Aufgrund des Flansches treten lokale Biegemomente in der Schale auf, die die nominelle Meridianspannung erhöhen, d. h., es treten Spannungskonzentrationen auf. In diesem Beitrag werden der Einfluss geometrischer Imperfektionen sowie der Einfluss der Flanschgeometrie quantifiziert. Es werden Empfehlungen für Flanschabmessungen und die Bemessung gegeben.